Continuing challenges of elephant captivity: the captive environment, health issues, and welfare implications - Catherine Doyle; Heather Rally; Lester O’Brien; Mackenzie Tennison; Lori Marino; Bob Jacobs (PeerJ, 2024)
Although the well-being of elephants in captivity is of paramount importance, the confinement of these long-lived, highly intelligent, and socially complex animals continues to present significant challenges. Here, we provide an overview of the current state of elephant confinement (primarily in the West) by examining captive facilities, improvements, and continuing problems, and the clinical/behavioral/neural issues that remain. Specifically, we examine quantitative and qualitative aspects of the enclosed space, sociocognitive factors, dietary differences, and health/welfare concerns (e.g., stereotypies, physical health, nutrition, reproduction, life expectancy). The challenges of the captive environment become especially salient when juxtaposed next to the complex, multifaceted characteristics of the elephant’s natural environment. Despite the best efforts of some facilities to improve the captive environment, serious welfare challenges remain. Such confinement issues thus raise important welfare and ethical concerns with regards to captive elephant well-being.